Effects of cerebellar transcranial direct current stimulation on attentional processing of the stimulus: Evidence from an event-related potentials study. (April 2016) - Mannarelli, Daniela; Pauletti, Caterina; De Lucia, Maria C.; Delle Chiaie, Roberto; Bersani, Francesco Saverio; Spagnoli, Francesco; Minichino, Amedeo; Currà, Antonio; Trompetto, Carlo; Fattapposta, Francesco
Abstract: Attentional processing consists of a set of processes that manage the flow of information through the nervous system and appropriately allocate attentional resources to relevant stimuli. Specific networks in the frontal and parietal regions appear to be involved in attention. The cerebellum has been identified as a subcortical structure that interacts with cortical brain areas, thereby controlling attentional processes. The aim of this study was to investigate the role of the cerebellum in attentional processing of the stimulus using a P300 Novelty task. We studied the effects of transcranial Direct Current Stimulation (tDCS) delivered over the left cerebellar hemisphere in cathodal, anodal and sham sessions on the P300 components in healthy subjects. Only cathodal cerebellar tDCS significantly reduced the amplitude of the N1, N2 and P3 components for both the target and novel stimuli. Moreover, N1 latency for all the stimuli was shorter after the cathodal tDCS session than after the sham or anodal sessions. These results point to a role of the cerebellum in attentional processing of the stimulus. The cerebellum may act indirectly by regulating and managing the activation and inhibition levels of the cortical areas involved in attentional networks. Highlights: Attentional processing was explored by Novelty P300 task prior to and after left cerebellar tDCS. N1 latency for all the stimuli was shorter after cathodal tDCS than after sham or anodal sessions. Cathodal cerebellar tDCS reduced the N1, N2 and P3 amplitudes to target and novel stimuli. The cerebellum influences indirectly the attentional processing. The cerebellum manages the activation levels of the cortical areas involved in attention.